The Impact of Video-Based and Interactive Learning on Improving the Practical Readiness of Culinary Arts Students in the Tourism Industry - Ngatmini; Nirmalasari; Lulu Fajarwati (Jurnal Manajemen Bisnis dan Pariwisata, 2026)
This study aims to examine the effectiveness of video-based tutorials and interactive media in improving the practical readiness of Culinary Arts students in the 4th Semester in table settings at Medan State University. This study addresses the challenges of improving students' practical skills in a structured learning environment, especially during distance or hybrid learning conditions, by integrating technology into traditional culinary education. A quasi-experimental research design was used involving 5 Semester 4 students enrolled in the Table Setting course. Participants were divided into control and experimental groups. The experimental group received learning through video tutorials and interactive media, while the control group received conventional face-to-face instruction. Data were collected using pre-test and post-test practical assessments, observational checklists, and student self-perception questionnaires. Statistical analysis, including paired t-tests and descriptive statistics, was conducted to compare perceived skill development and readiness between groups. Results showed that students exposed to video-based and interactive learning showed a significant improvement in practical readiness compared to the control group (p < 0.05). Observational assessments showed improved accuracy in table setting, proper application of table manners, and overall efficiency during practical exercises. Students also report higher confidence and readiness for practical assessments. The study highlights the potential of integrating digital media into culinary education to improve the acquisition of practical skills. Limitations include a single institution sample and short duration of interventions, which may affect the generalization of findings. This study provides empirical evidence supporting the use of video tutorials and interactive media in culinary arts education. Future research can explore the long-term impact and integration of augmented reality or virtual simulations for skills development.